Pengaruh Pemahaman Standar Akuntansi Pemerintahan Berbasis Akrual, Pemanfaatan Teknologi Informasi dan Komitmen Organisasi Terhadap Efektivitas Penyusunan Laporan Keuangan dengan Gaya Kepemimpinan Sebagai Pemoderasi pada Badan Peradilan Se-Aceh - Muthmainnah Muthmainnah; Hasan Basri (Jurnal Telaah dan Riset Akuntansi, 2017)
This study aimed to examine the effect of understanding of accrual-based government accounting standards, utilization of information technology, organizational commitment, leadership style towards the effectiveness of financial statements preparation either simultaniously or partially. The population in this experiment was the entire unitworks on Courts in Aceh Provincewith total population of 43 units. Primary data used in this studywas a questionnaire distributed directly to 86 respondents. The analytical method used in this study was the interaction regression analysis. The results of this study demonstrated an understanding of accrual-based government accounting standards, utilization of information technology, organizational commitment, leadership styles simultaniously and partially affecteds the effectiveness of the preparation of financial statements, while moderation not all strengthening the effectiveness of the preparation of the financial statements.KEYWORDS : Understanding of accrual-based government accounting standards, Utilization of information technology, Organizational commitment, Leadership style, the effectiveness of the preparation of the financial statements.